The police, crime, and economic theory: A replication and extension - Chamlin, Mitchell B. (American journal of criminal justice, 1996)
Based on insights garnered from rational choice theory, Loftin and McDowall hypothesize that there is likely to be a reciprocal relationship, over time, within jurisdictions between police force strength and crime. Contrary to expectations, their ARIMA analyses of the association between total police force employment and the total crime rate for Detriot during the period of 1926 to 1977 produce null findings. As a result, they conclude that rational choice models are too simplistic to explain the relationship between the agency size and crime. It is our contention that this conclusion might be premature. We suggest that a failure to disaggregate total police force employment into its component sectors may be masking substantial reciprocal effects. The present investigation employs ARIMA techniques to model the reciprocal relationship between total, patrol, and detective police employment and total, property, and personal, robbery crimes in Milwaukee for the years 1930 to 1987. Consistent with previous research we report null findings between total police employment and total crime rates. However, the findings also reveal significant reciprocal relationships between the disaggregated measures of police size and crime. The implications of these results for rational choice theory are discussed.